Effect of School-Based Educational Intervention on Childhood Obesity in Croatian Urban and Rural Settings - Sara Cobal; Darija Vranešić Bender; Jasenka Gajdoš Kljusurić; Ivana Rumora Samarin; Željko Krznarić (MDPI AG, 2024)
Background: Childhood obesity is a global public health concern. Development of effective public health interventions represents the only viable option for decreasing the prevalence of childhood obesity. The objective of this study was to assess the effectiveness of a school-based "PETICA-Play for Health" obesity prevention program in urban and rural areas in Croatia. Methods: This before-and-after study included 28 elementary schools in Croatia focused on pupils (n = 753, 2nd grade) and their guardians (n = 753) during the school year 2022/2023. "PETICA" multicomponent lessons and workshops (10) were implemented in the school curriculum and home settings (parents) as part of the intervention. Knowledge and lifestyle habit changes were evaluated via the questionnaire on knowledge and habits regarding nutrition and physical activity pre-/post-education. The Wilcoxon test for paired samples, Student's t-test (dependent and independent samples), multiple Mann Whitney U tests (p < 0.05), Spearman's correlation, and heatmaps were used. Results: The analysis showed a significant increase in acquired knowledge among pupils (both settings) and habits in the rural setting (increase in sports activities participation, breakfast, and vegetables consumption (p < 0.001, p = 0.003, p = 0.004)), decrease of sweets and salty snacks intake (p = 0.027, p = 0.011), and also, the link between parents' and children's physical activity levels (p = 0.028 vs. p = 0.022), emphasizing the importance of parents as healthy lifestyle role-models. Conclusion: The study shows that "PETICA" is an efficient school-based educational model that contributes to positive changes in children's knowledge and lifestyle habits that are a prerequisite for childhood obesity prevention.